Satisfaction determinants of airlines industry in Malaysia / Mohd Remie Mohd Johan ... [et al.] - Mohd Johan, Mohd Remie; Annuar, Nursyamilah; Joseph, Jechonias Sushant; Kalai Kumar, Sonika (Universiti Teknologi MARA, Perlis, 2020)
This study provides detailed information on customer satisfaction and decision making on choosing a full-service airline in Malaysia based on the number of complaints lodged to MAVCOM. To ensure the study was done with zero-errors, the information stated in this investigation were acquired from a targeted audience which has travelled for leisure purposes only to both domestic and international destinations. The aims of this study is to gives the airlines and edge to refine their customer service and to scrutinize their operations to avoid giving a chance to passenger to choose an alternate airline in Malaysia to suit their itinerary due to the failure in rectifying the inability in providing convenience towards their customers. This paper utilized a questionnaire to collect the data and was analysed by using Statistical Package for Social Science (SPSS). Multiple regression is used to find the causal effect of numerous independent variables towards the dependent variable. The results found that service quality, price, reliability (timeliness) and customer relationship management has a significant and positive contribution towards passenger selection of a full-service carrier in Malaysia.